THE EFFECTIVENESS OF CLUSTERING TECHNIQUE TOWARDS STUDENTS’ READING COMPREHENSION OF EXPLANATION TEXT (ELang | An English Language Education Journal, 2023)
The research paper entitled “The Effectiveness of Clustering Technique Towards Students’ Reading Comprehension of Explanation Text”. It is a quasi experimental research conducted at twelve grade students of SMA Al Qona’ah Baleendah. The aims of the research is to find out whether or not the clustering technique is effective to improve students' reading comprehension of the explanation text in SMA Al Qona’ah Baleendah. The sample of the research is 20 students of XII MIPA I for experimental group and 20 students of XII MIPA II for control group. The instruments are pre test and post test. The pre test was administered to know the students’ reading ability before the treatments and the post test was administered to students to measure whether or not there was progress in students’ reading comprehension. The result of the research showed that the students who taught by using the clustering technique get a higher score than the students who taught by using conventional method. It can be concluded that the result was proven by t-test calculation, where the t-observe is bigger than t-table. As the derived t = 3.252 exceeds the table critical value of t = 2.021, at p = 0.05 with Df = 38 (3.252 > 2.021). Therefore, the alternative hypotheses (Ha) is accepted, stating that there is significant difference in result between clustering technique and the conventional method in reading comprehension to the twelve grade of SMA Al Qona’ah Baleendah and the null hypotheses (Ho) is rejected. Thus it can be concluded the Clustering Technique is effective in improving students’ reading comprehension on explanation text